(untitled) (ABDIMAS: Jurnal Pengabdian Masyarakat, 2026)
Traditional weaving artisans in Tenganan Traditional Village possess significant potential to produce superior products based on local cultural heritage. However, limited adoption of digital marketing has resulted in conventional marketing practices, leading to restricted market reach and suboptimal sales performance. This community service program aims to enhance the knowledge and skills of weaving artisans through the implementation of digital marketing and the use of Augmented Reality (AR) as a modern marketing strategy. The implementation methods included observation and planning stages, educational sessions on the importance of digital marketing, practical training in the use of social media and marketplace platforms, as well as mentoring in the application of AR technology to present woven products interactively and engagingly. The activities were conducted using a participatory approach that actively involved the weaving artisan groups. The results indicate an improvement in the artisans’ understanding and skills in digital product marketing. The weaving groups in Tenganan Traditional Village are now able to utilize social media and marketplace platforms for product promotion and have gained insight into the potential of AR technology to enhance product attractiveness and expand market reach at the national level. The integration of digital marketing and AR is expected to strengthen the artisans’ competitiveness while supporting the preservation of traditional weaving culture in the digital era.